Optimum superheat utilization of extraction steam in double reheat ultra-supercritical power plants. (15th December 2015) - Xu, Gang; Zhou, Luyao; Zhao, Shifei; Liang, Feifei; Xu, Cheng; Yang, Yongping
Highlights: Two superheat utilization schemes of extraction steam are proposed. A comparative study of thermodynamic and techno-economic analyses is conducted. Two proposed schemes can both effectively utilize the superheat of extraction steam. More obvious energy saving effect is obtained at low load conditions. Abstract: Double reheat ultra-supercritical power plants have been receiving an increasing amount of attention because of their high thermal efficiency. However, the superheat degree of extraction steam in double reheat power plants is relatively high and results in a large temperature difference in the heat transfer process of the regenerative system. As a result, this impedes further improvement of the thermal efficiency of double reheat power plants. This paper presents two superheat utilization schemes of extraction steam in a double reheat ultra-supercritical power plant, where one scheme adopts outer steam coolers and the other employs a regenerative turbine. A comparative study of the two proposed schemes is conducted. Thermodynamic and techno-economic analyses are performed to reveal the energy saving effects of the proposed schemes. Thermodynamic analyses under partial load operation conditions are also presented. The results reveal the following. The power generation efficiency of the outer steam cooler scheme and the regenerative turbine scheme increases by 0.16 percentage points and 0.67 percentage points compared with a reference double reheat power plant, respectively. When the load is reduced, the energy saving effects of the proposed schemes become more obvious. The power generation efficiency increments of the outer steam cooler and the regenerative turbine schemes can reach 0.19 and 0.79 percentage points, respectively, at a 50% turbine heat acceptance load. The net annual revenues of the two schemes are 0.29 and 1.59 million USD, respectively. The results indicate that the two proposed schemes can both effectively utilize the superheat of extraction steam for double reheat ultra-supercritical power plants. In comparison, the regenerative turbine scheme is superior to the outer steam cooler scheme in terms of thermodynamic and techno-economic performance.